ANALISIS KARAKTERISTIK KAWASAN PERI URBAN DI KABUPATEN YALIMO PAPUA - Ivan Medwin; Janviter Manalu; Mujiati Mujiati (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
The peri-urban area is a dynamic area and continues to develop in various aspects along with the development of the city and the surrounding area, so that it can shift its rural appearance towards urban areas. The purpose of this study is to identify and analyze the characteristics of the peri-urban area based on physical, social and economic aspects in Yalimo Regency and to analyze regional development efforts and strategies according to the potential of Yalimo Regency, Papua.The research method used is quantitative and qualitative research, based on existing secondary data, namely the number and distribution of the population, density level, physical data and community economic data in Yalimo Regency, so that the classification of peri-urban areas (WPU) can be determined. SWOT analysis is used to determine the potential and obstacles/constraints of regional development. The results obtained are in terms of a). the physical aspect of Elelim District is included in Secondary Peri-urban, Apalapsili District is included in Rural Peri-urban, and Abenaho District is included in Secondary Peri-urban, b) social aspects of Elelim District, Apalapsili District and Abenaho District are included in Peri-urban Rural, c ) the economic aspects of Elelim District, Apalapsili District, and Abenaho District are included in the Peri-urban Rural.